Immune dysfunctions affecting bone marrow Vγ9Vδ2 T cells in multiple myeloma: Role of immune checkpoints and disease status - Giannotta, Claudia; Castella, Barbara; Tripoli, Ezio; Grimaldi, Daniele; Avonto, Ilaria; D’Agostino, Mattia; Larocca, Alessandra; Kopecka, Joanna; Grasso, Mariella; Riganti, Chiara; Massaia, Massimo (Frontiers in Immunology, 2022)
Introduction Bone marrow (BM) Vγ9Vδ2 T cells are intrinsically predisposed to sense the immune fitness of the tumor microenvironment (TME) in multiple myeloma (MM) and monoclonal gammopathy of undetermined significance (MGUS). Methods In this work, we have used BM Vγ9Vδ2 T cells to interrogate the role of the immune checkpoint/immune checkpoint-ligand (ICP/ICP-L) network in the immune suppressive TME of MM patients. Results PD-1+ BM MM Vγ9Vδ2 T cells combine phenotypic, functional, and TCR-associated alterations consistent with chronic exhaustion and immune senescence. When challenged by zoledronic acid (ZA) as a surrogate assay to interrogate the reactivity to their natural ligands, BM MM Vγ9Vδ2 T cells further up-regulate PD-1 and TIM-3 and worsen TCR-associated alterations. BM MM Vγ9Vδ2 T cells up-regulate TIM-3 after stimulation with ZA in combination with αPD-1, whereas PD-1 is not up-regulated after ZA stimulation with αTIM-3, indicating a hierarchical regulation of inducible ICP expression. Dual αPD-1/αTIM-3 blockade improves the immune functions of BM Vγ9Vδ2 T cells in MM at diagnosis (MM-dia), whereas single PD-1 blockade is sufficient to rescue BM Vγ9Vδ2 T cells in MM in remission (MM-rem). By contrast, ZA stimulation induces LAG-3 up-regulation in BM Vγ9Vδ2 T cells from MM in relapse (MM-rel) and dual PD-1/LAG-3 blockade is the most effective combination in this setting. Discussion These data indicate that: 1) inappropriate immune interventions can exacerbate Vγ9Vδ2 T-cell dysfunction 2) ICP blockade should be tailored to the disease status to get the most of its beneficial effect.